Factors affecting tea consumption pattern in an urban society in Isfahan, Iran - Rezaee, Elahe (J Educ Health Promot, 2016)
OBJECTIVE: To determine the tea consumption pattern in an urban society in Isfahan. METHODS: A descriptive, cross-sectional survey was carried out using questioner among 664 households who were selected by two steps cluster sampling. A questionnaire was developed including demographic questions, information on the quantity of tea intake by every member of the family, tea type, and tea brand preference. RESULTS: The individuals who prioritized black tea as their 1(st) choice were 90.1% of the total surveyed community. The average amount of tea consumed was calculated as 1243 ± 530 ml/day. The individuals who were between 36 and 45 and <15 years old were shown as the highest and the lowest tea consumers, respectively. Men significantly consumed more amount of tea than women did and married participants significantly used more amount of tea than singles (P < 0.05). The number of the family members, though, had no impact on tea consumption (P > 0.05). Brand preference of tea showed that the individuals who prioritized Ahmed brand as their 1(st) choice constituted 44% of the total participants. CONCLUSION: Tea consumption pattern in an Iranian sample is specific. Despite of the huge evidence on the green tea benefits, this type of tea has very low popularity and among the available black tea brands, the imported ones are the most preferred.